Dilution sampling and analysis of particulate matter in biomass-derived syngas - WANG, Xiaoliang; ROBBINS, Curtis; HOEKMAN, S. Kent; CHOW, Judith C.; WATSON, John G.; SCHUETZLE, Dennis (Frontiers of environmental science & engineering, 2011)
Thermochemical biomass gasification, followed by conversion of the produced syngas to fuels and electrical power, is a promising energy alternative. Real-world characterization of particulate matter (PM) and other contaminants in the syngas is important to minimize damage and ensure efficient operation of the engines it powers and the fuels created from it. A dilution sampling system is demonstrated to quantify PM in syngas generated from two gasification plants utilizing different biomass feedstocks: a BioMax ®15 Biopower System that uses raw and torrefied woodchips as feedstocks, and an integrated biorefinery (IBR) that uses rice hulls and woodchips as feedstocks. PM 2.5 mass concentrations in syngas from the IBR downstream of the purification system were 12.8-13.7 µg·m -3, which were significantly lower than the maximum level for catalyst protection (500 µg·m -3) and were 2-3 orders of magnitude lower than those in BioMax ®15 syngas (2247-4835 µg·m -3). Ultrafine particle number concentration and PM 2.5 chemical constituents were also much lower in the IBR syngas than in the BioMax ®15. The dilution sampling system enabled reliable measurements over a wide range of concentrations: the use of high sensitivity instruments allowed measurement at very low concentrations (~1 µg·m -3), while the flexibility of dilution minimized sampling problems that are commonly encountered due to high levels of tars in raw syngas (~1 g·m -3).